Practices of Introduction of Complementary Feeding and Iron Deficiency Prevention in the Middle East and North Africa. Issue 4 (October 2018) - Lifschitz, Carlos H.; Miqdady, Mohamad; Indrio, Flavia; Haddad, Joseph; Tawfik, Eslam; AbdelHak, Akbari; Mouane, Nezha; Salah, Mohamed; Khatami, Katayoun; Olang, Beheshteh; Vandenplas, Yvan
ABSTRACT: Background: Iron deficiency (ID) with or without anemia is associated with impaired mental and psychomotor development. Given the paucity of information on physicians' knowledge and practices on iron (Fe) supplementation and impact of ID in the Middle East and North Africa, it was felt important to conduct a survey. Method: A group of expert physicians developed a questionnaire that was randomly distributed among Middle East and North Africa doctors to assess their knowledge and practices on introduction of complementary feeding, impact of ID, its prevention, and their impression on prevalence of ID. Descriptive statistics were used. Results: We received 2444 completed questionnaires. Thirty-nine percent of physicians do not follow the European Society for Paediatric Gastroenterology, Hepatology and Nutrition guidelines regarding age of introduction of complementary feedings. Approximately 62% estimate the prevalence of ID anemia to be 40% to 70%; however, only 17% always monitor hemoglobin between 9 and 12 months of age, 43% do so "almost" always, whereas 36% do so "rarely" or (4%) "never." For the prevention of ID in infants older than 6 months of age, almost all recommend introducing Fe supplements. Ninety-seven percent agree that untreated ID during infancy may have long-term negative effects on cognitive function, whereas 53.26% consider that Fe-enriched infant cereals result in staining of the baby teeth, constipation, and dark stools. Conclusions: Although there is awareness of the impact of ID, there are some misconceptions regarding age of introduction of complementary feedings, surveillance of Fe status, and side effects of Fe-enriched infant cereals. There is a need for educational initiatives focusing on prevention of Fe deficiency. Abstract : Supplemental Digital Content is available in the text